2008
DOI: 10.1021/bi702126p
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Nucleophilic Character in the Cys25/His159 Ion Pair of Papain Involves Trp177 but Not Asp158

Abstract: Studies on papain (EC 3.4.22.2), the most thoroughly investigated member of the cysteine proteinase superfamily, have contributed substantially to our understanding of the roles of noncovalent interactions in enzyme active center chemistry. Previously, we reported evidence that the long-held view that catalytic competence develops synchronously with formation of the catalytic site (Cys25)-S-/(His159)-Im+H ion pair is incorrect and that conformational rearrangement is necessary for each of the partners to play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 27 publications
2
55
0
Order By: Relevance
“…The factors that govern the properties of the artificial, buried Glu-Lys pair are the same ones that govern the properties of ionizable groups in the active sites of enzymes (38)(39)(40). Therefore, the successful engineering of a Glu-Lys pair in the hydrophobic interior of a highly stable form of SNase is also significant because it constitutes an empirical demonstration that buried ion pairs and charge clusters resembling enzymatic active sites can be engineered in the hydrophobic interior of a scaffold protein.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that govern the properties of the artificial, buried Glu-Lys pair are the same ones that govern the properties of ionizable groups in the active sites of enzymes (38)(39)(40). Therefore, the successful engineering of a Glu-Lys pair in the hydrophobic interior of a highly stable form of SNase is also significant because it constitutes an empirical demonstration that buried ion pairs and charge clusters resembling enzymatic active sites can be engineered in the hydrophobic interior of a scaffold protein.…”
Section: Discussionmentioning
confidence: 99%
“…The side chain of the latter assumes the role of the oxyanion hole of serine peptidases in stabilizing the tetrahedral intermediate (2) , whereas the former plays a role analogous to Asp in the catalytic triad of serine peptidases, forming a hydrogen bond to His159, but is not absolutely essential for catalysis (3) . Recent evidence, however, suggests an important role for the adjacent Trp177 in the generation of the nucleophilic character of the catalytic diad (4) .…”
Section: The Active Center Of Papain-like Peptidasesmentioning
confidence: 99%
“…There is considerable variation among members of the papain family, however, in substrate specificity and catalytic-site reactivity [81,[153][154][155][156][157][158], which reveals that this view is correct only for low-resolution aspects of the mechanism, such as the roles of the cysteine and histidine components of the catalytic-site ion pair. The results of detailed mechanistic investigations on papain and some of its natural variants (discussed in [44,45]) have revealed that papain exhibits characteristics at one end of a spectrum of chemical behavior with actinidin at the other, and with caricain and ficin occupying intermediate positions. Key results include the identification of kinetically influential pK a values, both those associated with the catalytic site (Cys25)-S À /(His159)-Im þ H ion pair (papain numbering) and others more remote [44], the coupling of molecular recognition interactions with catalytic site chemistry, and postacylation protein dynamics.…”
Section: Cysteine Proteinasesmentioning
confidence: 99%
“…Studies using reactivity probes, particularly disulfides containing the 2-mercaptopyridine leaving group as two-protonic-state electrophiles [41,81], including substrate-derived probes [20,44], a 4-pyrimidyl probe that remains unprotonated over a wide range of low pH values [44] and 4-chloro-7-nitrobenzofurazan [159], pHdependent kinetics [42], computer modeling including normal mode analysis [45] and electrostatic potential calculations [81], and natural variants of the papain family, have changed the perception of the catalytic mechanisms of these enzymes and of the influence of binding interactions and electrostatic effects (see [20,44] for detailed discussion).…”
Section: Cysteine Proteinasesmentioning
confidence: 99%
See 1 more Smart Citation